1971
DOI: 10.1083/jcb.51.3.826
|View full text |Cite
|
Sign up to set email alerts
|

BASAL BODIES, BUT NOT CENTRIOLES, IN NAEGLERIA

Abstract: Amebae of Naegleria gruberi transform into flagellates whose basal bodies have the typical centriole-like structure . The amebae appear to lack any homologous structure, even during mitosis . Basal bodies are constructed during transformation and, in cells transforming synchronously at 25°C, they are first seen about 10 min before flagella are seen . No structural precursor for these basal bodies has been found . These observations are discussed in the light of hypotheses about the continuity of centrioles .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
88
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 45 publications
12
88
0
1
Order By: Relevance
“…Gould and Borisy [1977] or more recently Afonso et al [2007] have indicated that retroviruses target the centrosome (and sometimes hijack centrosomal functions), which is consistent with centriolar origin from a retrovirus. Centrioles self-assemble de novo in ameboflagellates [Fulton and Dingle, 1971] and during male gametogenesis in aquatic ferns and in Gingko, where they disappear after fertilization. In Chlamydomonas, centrioles can form either by a templated pathway with pre-existing centrioles or by de novo assembly that is normally repressed when pre-existing centrioles are present [Marshall et al, 2001].…”
Section: Viral-like Replication and Self-assemblymentioning
confidence: 99%
“…Gould and Borisy [1977] or more recently Afonso et al [2007] have indicated that retroviruses target the centrosome (and sometimes hijack centrosomal functions), which is consistent with centriolar origin from a retrovirus. Centrioles self-assemble de novo in ameboflagellates [Fulton and Dingle, 1971] and during male gametogenesis in aquatic ferns and in Gingko, where they disappear after fertilization. In Chlamydomonas, centrioles can form either by a templated pathway with pre-existing centrioles or by de novo assembly that is normally repressed when pre-existing centrioles are present [Marshall et al, 2001].…”
Section: Viral-like Replication and Self-assemblymentioning
confidence: 99%
“…Switching between flagella-based swimming motility and actin-based gliding motility might be an ancient strategy for adapting to different environments. For instance, the excavate Naegleria gruberii can interconvert between a flagellate and an amoeba depending on whether it is placed in a liquid environment or associated with a solid substrate [64,[69][70][71][72]. In Naegleria flagellates, the two centrioles anchor microtubule roots that contribute to cell morphology in association with a rigid cortex of actomyosin.…”
Section: (A) the Amorphean Ancestormentioning
confidence: 99%
“…FIGURE 13 Ouchterlony immunodiffusion test of antiserum to rootlet protein . The antiserum to rootlet protein, well B, was assayed against all the SDS-solubilized proteins of a typical rootlet preparation, well A .…”
Section: Rootlet Localization In Vivomentioning
confidence: 99%
“…The rapid, controlled, and highly reproducible cellular transformation of Naegleria has been promoted as a model for the study of eukaryotic cell differentiation (4,11), and the sequence of development of both flagella and basal bodies has been elucidated using this model (5,12,13) . Because organelle differentiation can be precisely timed during flagellate differentiation (4,12), and the organelle number can be experimentally manipulated (3,6), a study of rootlet development correlated with basal body and flagellum development also becomes feasible in this system .…”
mentioning
confidence: 99%